2014
DOI: 10.1021/jp5069895
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Electronic Properties of Biphenylene Based Functionalized Nanoribbons and Sheets

Abstract: By means of first principle calculations, we have performed a theoretical characterization of the stability and electronic properties of sheets and nanoribbons that were recently synthesized employing octafunctionalized biphenylenes as building blocks. We found that the biphenylene sheet has a strong metallic character that is difficult to inhibit employing low levels of functionalization. Hydrogenation at full coverage induces a metal to insulator transition, but the band gap opened is very large, i.e., 6.6 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…26,27,[29][30][31][32] membranes have also been the subject of several theoretical studies. [34][35][36][37][38][39] These have mainly focused on the electronic properties of the BP membranes and its ribbons and nanotubes where it was found that the pristine sheet is metallic with no band gap. Denis et al 38 investigated hydrogen storage on lithium and calcium decorated BP membrane.…”
Section: Introductionmentioning
confidence: 99%
“…26,27,[29][30][31][32] membranes have also been the subject of several theoretical studies. [34][35][36][37][38][39] These have mainly focused on the electronic properties of the BP membranes and its ribbons and nanotubes where it was found that the pristine sheet is metallic with no band gap. Denis et al 38 investigated hydrogen storage on lithium and calcium decorated BP membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Biphenylene is predicted to be metallic in the form of a sheet or tube [38] but possessing a band gap in the form of ribbon [38] or by functionalization. [35] Biphenylene sheet can be used for hydrogen storage and in Lithium Ion Batteries (LIB) as it is predicted to adsorb lithium significantly stronger than graphene and graphyne. [34] A recent study suggested potential application of biphenylene-based nanoribbons in electronics and optoelectronics in the visible range.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Schlütter et al reported recently that they were able to synthesize octafunctionalized biphenylene GNRs [33]. Another possibility is the combination of these geometries with functionalization [34] that can lead to interesting effects regarding gas adsorption [35]. The new generation of electronics may also be facilitated by producing any of the above structures using boron nitride (BN) or some combination of carbon, boron, and nitrogen atoms [36,37].…”
Section: Introductionmentioning
confidence: 99%